SUBCLINICAL HYPOTHYROISIS AS A RISK FACTOR OF SEVERE FORMS OF TRICHOPHYTIES (Academia Science Repository, 2023)
The problem of elimination of goiter endemia, prevention of hypothyroidism, including subclinical hypothyroidism (SH), is currently a priority in medicine, including Europe, Asia, America and other continents.